Marriage and other psychological stressors in the causation of psychiatric disorder - Mullick, Mohammad S. I.; Algin, Sultana; Ahmed, Helal Uddin; Majumder, Atiqul Haq (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The aim of this study was to compare the specific psychiatric diagnosis, frequency, and types of stressors, and the level of awareness about marriage law between married (cases; n=80) and unmarried girls (control; n=80) with one or more psychiatric disorders below the age of 18 years. The psychiatric diseases were diagnosed according to Axis One of ICD-10 clinical diagnoses of multi-axial classification of childhood and adolescent psychiatric disorder. Psychosocial stressors were considered on the basis of Axis Five of this classification. Of the cases, major depressive disorder was the highest (n=47) and next was a dissociative (conversion) disorder (n=24). Among the controls, generalized anxiety disorder (n=31) was the most prevalent followed by obsessive-compulsive disorder (n=17). The difference was highly significant (p>0.001). The cases reported a significant excess of psychosocial stressors than that of the controls to the onset of the psychiatric disorder. All the cases had associated stressors. In contrast, 77 out of 80 control patients had stressors. Marriage itself played as a stressor in the 78 cases. Beside this, other highly frequent stressors were marital discord followed by drop out from study and trouble with in-laws. Among the controls, the highest reported stressor was increased academic workload and next two commonest stressors were poor academic performance and discord with peers. Interestingly, 52.5% of the cases were having knowledge about the law on the age of marriage and that was 32.5% among the controls. It was significant that most of the girls breached their continuity of education after marriage (p>0.001). In conclusion, psychosocial stressors including marriage have a causal relationship with depressive and conversion disorder.